Recent vitamin research - Briggs, Michael H, ed. (CRC press Boca RatonUS, 1984)
Presents the results of recent research into vitamin biochemistry, physiology and nutrition. Discusses specific vitamins and their responses to children's disorders, the parathyroid hormone in bone calcification, infectious diseases, the common cold, pregnancy and intrauterine growth, cancer, oral contraceptives, and neutral tube defects.